KOMUNIKASI KELOMPOK DAN KESEJAHTERAAN SOSIAL (Studi Deskriptif Kualitatif Tentang Komunikasi Kelompok Karang Taruna Mekar Remaja dalam Meningkatkan Kesejahteraan Sosial di Dusun Grasak Kismoyoso Boyolali) - Djaya, Tika Ristia (KOMUNITAS, 2013)
The objectives of the research are to study about group communication which are conducted by the members of ââMekar Remajaââ youth association and to know about the roles of its members inÂ improvingÂ socialÂ welfare.Â ThisÂ researchÂ usedÂ descriptiveÂ andÂ qualitativeÂ methodÂ toÂ explain about various phenomena that occur in the field. The location of this research is in Grasak village Kismoyoso Boyolali, the data of this research wereÂ gained by doing interview, observation, and documentation. Sampel of this data are four membersof ââMekar Remajaââ youth association and two people who are not members of this association.The result of analysis which is conducted by the writer are: group communication which are conducted by ââMekar Remajaââ youth association isÂ two ways communications that are: face to faceÂ communication,Â andÂ communicationÂ throughÂ media (handÂ phoneÂ andÂ invitation)Â and conducting regular meeting every 35 days, this event has been effective. Another activities which areÂ heldÂ byÂ ââMekarÂ RemajaââÂ youthÂ associationÂ such as:Â entrepreneurship,Â communityÂ service, âsinomanâ, sport activities, ââhalal bi halal, ââIdul Adhaââ, and held many events to celebrate the independenceÂ day.Â MembersÂ ofÂ ââMekarÂ RemajaââÂ youth associationÂ canÂ maintainÂ theÂ group communicationÂ whichÂ isÂ alreadyÂ effective,Â andÂ improveÂ theÂ entrepreneurÂ activitiesÂ andÂ other positive activities in order to increase the socialwelfare in Grasak village Kismoyoso Boyolali.